Penanganan Kasus International Child Abduction di Indonesia: Studi Kasus Penculikan Ezekiel Gionata Purba & Penculikan Enrico Johannes Susanto Carluen - Ershiano, Dhani; Hertanto, Ari Wahyudi; Utomo, Benedetto Setyo Satrio (UI Scholars Hub, 2025)
Child protection, particularly in preventing and addressing cases of international child abduction, is an obligation of all states. This phenomenon frequently occurs in Indonesia when a foreign-national parent, following divorce, unilaterally takes their biological child abroad in violation of court-granted custody, guardianship, and/or access rights of the other parent. Currently, Indonesia lacks adequate legal provisions to prevent and resolve cases of international child abduction. Moreover, Indonesia has not yet acceded to the Hague Convention on the Civil Aspects of International Child Abduction 1980 (“the 1980 Hague Convention”). This convention establishes a legal mechanism to ensure the prompt return of children to their country of habitual residence while protecting the lawful rights of parents. This paper analyzes legal protections for victims of international child abduction under the 1980 Hague Convention and urges the Indonesian government to promptly accede to the convention to address legal gaps and safeguard the best interests of the child.